PERSEPSI DAN MOTIVASI MASYARAKAT LOKAL TERHADAP PROGRAM TRANSMIGRASI PASCA KONFLIK DI KABUPATEN ACEH BARAT PROVINSI ACEH - Riki Abadi,; Su Rito Hardoyo,; Sri Rum Giyarsih (Universitas Gadjah Mada, 2016)
This study aims to explore the perception and motivation of the local community toward post-conflicttransmigration program in West Aceh. The research method used in this article is a combination of bothqualitative and quantitative approach. The technique of processing data uses statistical test of crosstabulation (crosstab), Chi-Square, and Spearman correlation test. For collecting samples, this article usespurposive sampling method with the total sample size of 120 respondents. The results shows that therelationship between the level of perception and the motivation for transmigration are high enough andpositively correlated −the more increasing perception of the local community toward the transmigrationprogram, the more increasing motivation to people for transmigration. Meanwhile, the motivationwhich affects the community to join the transmigration program is the motif of independence.